TGF-β and FRF-21: association with coronary artery disease in patients with type 2 diabetes and obesity - Teona A. Shvangiradze (Ожирение и метаболизм, 2017)
Backgraund: Obesity and type 2 diabetes mellitus (T2DM) are associated with with an increased risk of cardiovascular disease (CVD) and coronary artery disease (CAD), in particular. Obesity lead to several fibrotic processes, including activation of transforming growth factor β (TGF-β). Recent data indicate the involvement of Fibroblast growth factor 21 (FGF-21) as an important metabolic regulator, and even biomarker of metabolic changes in obesity and T2DM. Impact of metabolic dysregulation that accompany obesity and T2DM in CAD development remain a great challenge. Aims: To study TGF-β and FGF-21 level in patients with obesity and T2DM. Materials and methods: TGF-β and FGF-21 were identified in peripheral blood samples of 66 patients with obesity, aged 48-65 years. 1st group included 21 patients with CHD and T2DM; 2nd group (22 patients)- with T2DM and excluded CHD; 3rd group (20 patients) with normal glucose metabolism and excluded CHD. Results: TGF-β was lower in patients with CHD (group 1) than in the group of "metabolically healthy" obesity (p=0.022). TGF-β in patients with T2DM negatively correlated with LDL cholesterol (r=-0.426, p=0.038) the degree of internal carotid artery stenosis (r=-0.426, p=0.024). Patients with verified CHD had a negative correlation with the processes of heart muscle remodeling (thickness of the left ventricular posterior wall (r=- 0.386, p=0.029) interventricular septum (r=-0.335, p=0.031). All patients with obesity had significantly increased level of FGF-21 compared with the control group (p=0.031) FGF-21 positively correlated with BMI (r=0.473, p=0.033) Conclusions: TGF-β has negative correlations with the factors that can influence prognosis and the severity of the CVD/. There were found correlations of FGF-21, TGF-β with pathological angiogenesis and changes in normal cardiac geometry in obesity, T2DM and CAD.